Recent advances in biodegradable polymers for sustainable applications - Aya Samir; Fatma H. Ashour; A. A. Abdel Hakim; Mohamed Bassyouni (npj Materials Degradation, 2022)
Abstract The interest in producing biodegradable polymers by chemical treatment, microorganisms and enzymes has increased to make it easier to dispose after the end of its use without harming the environment. Biodegradable polymers reported a set of issues on their way to becoming effective materials. In this article, biodegradable polymers, treatment, composites, blending and modeling are studied. Environmental fate and assessment of biodegradable polymers are discussed in detail. The forensic engineering of biodegradable polymers and understanding of the relationships between their structure, properties, and behavior before, during, and after practical applications are investigated.